Clinicopathologic analysis of renal cell carcinoma containing Intratumoral fat with and without osseous metaplasia - Zhaoying Xian; Jason O. Orien; Geoffrey N. Box; Debra L. Zynger (BMC, 2020)
Abstract Background There is minimal information regarding the prevalence of intratumoral adipose in renal cell carcinoma (RCC), and no study has assessed the impact of intratumoral adipose on the preoperative imaging diagnosis. The aim of this study was to investigate the prevalence and histopathologic characteristics of entrapped adipose with or without osseous metaplasia in RCC nephrectomy specimens and to determine if this finding impacted the preoperative imaging interpretation. Methods 704 RCC specimens were prospectively evaluated for entrapped adipose and osseous metaplasia (423 partial nephrectomies, 281 total nephrectomies; 327 pT1a, 377 ≥ pT1b; 510 clear cell, 119 papillary, 30 chromophobe, 22 clear cell papillary, 23 other). Imaging reports were obtained, and the presence of intratumoral fat or calcification and the radiologic diagnostic impression were recorded. Results 3% (n = 21) contained microscopically identified intratumoral adipose, with a similar frequency in the main histologic subtypes (p = 0.76). Mean metaplastic deposit size was 0.4 cm, mean deposit to capsule distance 0.2 cm, and 29% involved the tumor capsule. Histologically identified adipose was infrequently noted via imaging (13%), and only 1 case with histologically identified metaplasia had a radiologic diagnostic differential of angiomyolipoma (1/704, 0.1%). Conclusion While intratumoral adipose and/or osseous metaplasia can be observed within RCC, it is extremely rare for the radiologic diagnostic impression to have been confounded by histologically identified entrapped adipose. Awareness that metaplastic deposits are usually near the tumor capsule and may be minute could help prevent errors in diagnosis or staging.